Biografi Rakyat Kecil, Sutikno: 1980-2018 Pendekatan Sejarah Post-Strukturalisme - Khoirul Munir, Akhmad; Wijaya, I Nyoman; Sukiada, I Nyoman (Humanis; Vol 24 No 2 (2020), 2020)
According to Kuntowijoyo writing biography can also be implemented against a person who comes from the unknown or participants. On that basis, study this takes up figure named Sutikno, a seacoast origin Bayuwangi East Java which currently domicile in Denpasar Bali by work as a mechanic motorcycle. A profession Sutikno will be the entrance in analysis, with an emphasis how he was that of a migrant (seacoast) generally in Bali can work as a mechanic workshop motorcycles with income that relatively success. By wearing a method/methodology Genealogi and theories post-strukturlism, especially the undirected Structural Generative Pierre Bourdieu and the Discourse-(Knowledge-Power )-Discipline Michel Foucault as a thought, the three had obtained. drawing conclusions. 1) With hard work and discipline, patient and keep trying not to despair Sutikno managed to achieve success even though through various obstacles and problems. 2) Factors behind the success of Sutikno mainly came from habitus and discipline and social private ownership of capital as a replacement for other capital. 3) Implication after sutikno pillars of success, that is a change from a social lower middle middle-class process for social climbed the stairs, characterized by differentiation consumption of goods that more luxurious and diverse than ever before.